Mobile Parenting Training Program Based on a Ubiquitous Learning Context to Improve Parenting Skill: The Moderating Role Parental Locus of Control - Yafie, Evania; Ashari, Zakiah Mohamad; Samah, Norazrena Abu (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The lack of knowledge about parenting has led to several cases of violence against children. Providing training on parenting skills is a possible solution. This study was presented with the aim of knowing the effectiveness of a mobile parenting training program based on ubiquitous learning to improve parenting skills moderated by parental locus of control. This study used a quasi-experimental design with control and experimental groups. Sampling in this study used purposive sampling with the following criteria for parents: 1) Having children aged 3-6 years, 2) Parents experiencing parenting problems, 3) Children experiencing developmental delays, 4) Willing to participate in the training program to completion. The tests used in this study include testing the validity and reliability of the instrument, classical assumption test, homogeneity test, and hypothesis testing using Two Way Anova parametric statistics. The results of this study can be concluded that a mobile parenting training program based on unbiquitous learning moderated by a good parental locus of control can improve parenting skills in parents.